Representations of ICTs in a migrant environment: the case of the Château-Rouge “communication shops” - (:unkn) unknown (My University, 2004)
Since the start of 2001, certain Parisian districts have seen the flourishing of “communication shops”: these points of sale offer international telephone services, mobile phone plans and accessories, access to transmitting faxes and reception, and thanks to ADSL, of microcomputers connected to the Internet. They are inspired by the model of African taxiphones or telecentres, created a few months earlier, notably in Dakar.These places of private economy join the line of collective access devices to communication technologies and networks: public telephone booths, information experiments by minitel within administrations in the 80s, interactive terminals associated with the museum visit, and more recently, multimedia public spaces, places of initiation to the Internet labeled in the late 90s as part of PAGSI.The survey of the locations of these shops in part of the 18th district of Paris shows their particular concentration in the perimeter of "Château-Rouge", a district inhabited by an immigrant population of very diverse origins, and immigrant centrality organized around a exotic market with an international reputation, known as the “African market”.This observation leads to questioning the role of Information Technologies in the structuring of the identity of migrant populations, and in particular of the diasporic feeling, that is to say the collective awareness of a transnational identity, nourished by the feeling to be "other" within the host nation. According to Dominique Wolton, optimizing international communication flows does not naturally lead to better mutual understanding. These market devices will therefore be approached from the angle of the anthropology of contemporary worlds by Marc Augié, according to which the consciousness of identity and otherness, at the heart of ethnological thought, is no longer only built on distance geographic and traditional "exoticism".Three tracks are explored:• That of the creation of a migrant p
Keywords: African Research